Possibilities of Using Zeolites Synthesized from Fly Ash in Adsorption Chillers - Agata Mlonka-Mędrala; Tarikul Hasan; Wojciech Kalawa; Marcin Sowa; Karol Sztekler; Moises Luzia Pinto; Łukasz Mika (Energies, 2022)
Adsorption chillers produce cold energy, using heat instead of electricity, thus reducing electrical energy consumption. A major industrial waste, fly ash, can be converted to zeolite and used in adsorption chillers as an adsorbent. In this research, three different types of zeolites were synthesised from fly ash via a hydrothermal reaction in an alkaline solution (NaOH). The obtained samples (Na-A zeolites) were modified with K2CO3 to increase the water adsorption capacity of these samples. Phase and morphology analyses shows that desired zeolites formed properly but other crystalline phases also exist along with nonporous amorphous phases. The determined specific surface areas for Na-A zeolite (12 h) and Na-A zeolite (24 h) are 45 m2/g and 185 m2/g respectively, while the specific surface area for synthesized 13X zeolite is almost negligible. Water-isotherm for each of these samples was measured. Considering the application of adsorption chillers, average adsorption capacity was very low, 1.73% and 1.27%, respectively, for the two most probable operating conditions for synthesized 13X zeolite, whereas no water was available for the evaporation from Na-A zeolite (12 h) and Na-A zeolite (24 h). This analysis implies that among the synthesized materials only 13X zeolite has a potential as an adsorber in sorption chillers.